EFEK PENYIMPANAN SECARA KRIOPRESERVASI PADA JENIS DAN LAMA PERENDAMAN KRIOPROTEKTAN DENGAN PERBEDAAN KONDISI BIJI TERHADAP VIABILITAS BENIH MANGGIS (Garcinia mangostana L.) - Dede Suhendra (UNIVERSITAS LABUHANBATU, 2014)
Effect Storage In Criopreservasi On Type And Old South Crioprotektan Different Conditions Of Seeds Against Viability of Mangosteen Seeds (Garcinia mangostana L.). The aim of the study was to determine the type, duration of soaking and the different conditions of mangosteen seeds and their interaction with the viability of mangosteen seeds (Garcinia mangostana L.). This research was carried out at the Laboratory of Applied Sciences in Seed Technology of Labuhanbatu College of Agricultural Sciences (STIPER), starting March to July 2018, using factorial randomized block design with 3 treatment factors namely cryoprotectant type, cryoprotectant immersion and mangosteen fruit flesh. Parameters observed were normal sprouts (%), abnormal sprouts (%), dead seeds (%). The results showed that the highest application of the parameters was the use of non-fruit flesh with cryoprotectant PVS2 and 180 minutes soaking time. The results of the research were used to develop mangosteen seed storage for the needs of the community, especially mangosteen farmers in Indonesia. Keywords : crioprotektan, criopreservasi, mangosteen seeds